Category-based or piecemeal-based processing? A dual model of web-mobile service extension behavior. Issue 5 (10th April 2019) - Gong, Xiang; Zhang, Kem Z.K.; Chen, Chongyang; Zhao, Sesia J.; Lee, Matthew K.O.
Abstract : Purpose: The advancements of mobile technologies and devices have greatly facilitated the extension of online services from web to mobile environments. Drawing on the categorization theory, the purpose of this paper is to explore the impact of perceived entitativity on users' web-mobile service extension behavior. The research model considers how perceived entitativity serves as a category cue to link the category- and piecemeal-based processing and shape users' adoption of extended mobile services. Design/methodology/approach: An online survey ( n =552) was conducted to empirically test the model. The data were analyzed by structural equation modeling approach. Findings: The results offer two major findings. First, performance expectancy, perceived controllability and subjective norm are important antecedents of users' usage intention. Second, perceived entitativity has three types of effects on usage intention: it exerts a direct and positive influence on usage intention; it indirectly facilitates usage intention through increasing PE and perceived controllability; and it moderates the relationship between subjective norm and usage intention. Originality/value: This study contributes to the literature by taking into account the interplay of category- and piecemeal-based processing to understand consumers' web-mobile service extension behavior.